2018
DOI: 10.1021/acs.est.7b05059
|View full text |Cite
|
Sign up to set email alerts
|

Development and Comparison of Air Pollution Exposure Surfaces Derived from On-Road Mobile Monitoring and Short-Term Stationary Sidewalk Measurements

Abstract: Land-use regression (LUR) models of air pollutants are frequently developed on the basis of short-term stationary or mobile monitoring approaches, which raises the question of whether these two data collection protocols lead to similar exposure surfaces. In this study, we measured ultrafine particles (UFP) and black carbon (BC) concentrations in Toronto during summer 2016, using two short-term data collection approaches: mobile, involving 3023 road segments sampled on bicycles, and stationary, involving 92 sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 27 publications
4
65
0
Order By: Relevance
“…First, road traffic might be measured as real time traffic recorded specifically during the time span of the study [32,33], estimations of daily traffic volume [34][35][36], or the type of roads taken by the cyclist [19,28,29]. In all cases, road traffic is associated with cyclists' greater exposure to air and noise pollution.…”
Section: Conceptual Framework For Modelling Cyclists' Multi-exposurementioning
confidence: 99%
“…First, road traffic might be measured as real time traffic recorded specifically during the time span of the study [32,33], estimations of daily traffic volume [34][35][36], or the type of roads taken by the cyclist [19,28,29]. In all cases, road traffic is associated with cyclists' greater exposure to air and noise pollution.…”
Section: Conceptual Framework For Modelling Cyclists' Multi-exposurementioning
confidence: 99%
“…Nieuwenhuijsen MJ et al (2015) [34] found a lower correlation between LUR estimates at home and personal BC values during commuting (r = 0.32) than the one we found (r = 0.74). Furthermore, Minet L et al (2018) [37] compared BC LUR derived surfaces (100 × 100 m grid) to personal exposure measures finding that the latter (median = 1764 ng/m 3 ) were underestimated by the model (median = 1469 ng/m 3 ). This result is comparable with our findings showing that short-term high exposure events are very hard to catch with a LUR approach.…”
Section: Discussionmentioning
confidence: 99%
“…A recent effort to outfit Google street cars across several US cities has also been successful in mapping fine-scale urban pollution gradients [24,25,28,29]. The importance of combining these mobile platforms with fixed-site platforms to derive highly resolved spatial pollution maps and related pollutant exposure metrics is a very active area of research [30][31][32]. In many cases, mobile air pollution monitoring studies describe short-term or seasonal campaigns.…”
Section: Overview Of Recent Mobile Urban Air Quality Studiesmentioning
confidence: 99%
“…Identifying the distribution of emission sources, in conjunction with monitoring the spatial distribution of pollutant exposure, is a necessary first step towards assessing potential health outcomes for vulnerable populations. research [30][31][32]. In many cases, mobile air pollution monitoring studies describe short-term or seasonal campaigns.…”
Section: Sociodemographic and Emission Characteristicsmentioning
confidence: 99%